2017
DOI: 10.1063/1.4975345
|View full text |Cite
|
Sign up to set email alerts
|

Oxides formation on hydrophilic bonding interface in plasma-assisted InP/Al2O3/SOI direct wafer bonding

Abstract: Successful direct wafer bonding between InP and silicon-on-insulator (SOI) wafers has been demonstrated by adopting a 20-nm-thick Al2O3 as the intermediate layer. A detailed investigation on the property of the bonding interface is carried out. Water contact angle test reveals an improved hydrophilicity for both the InP and the Al2O3/SOI wafers after oxygen plasma surface activation. X-ray photoelectron spectroscopy is employed to characterize the bonding interface before and after the wafer bonding process. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The slow scan results of In-3 d peak of sample grown at 480 °C (see Fig. 2 c) can be deconvolved into three peaks at 443.5, 442.3, and 444.4 eV, which are ascribed to InP, In 2 O 3, and InPO 4 [ 41 , 42 ], respectively. Based on the relative intensity, the weights ratio of the above compounds is 31.0%, 48.7%, and 20.3%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The slow scan results of In-3 d peak of sample grown at 480 °C (see Fig. 2 c) can be deconvolved into three peaks at 443.5, 442.3, and 444.4 eV, which are ascribed to InP, In 2 O 3, and InPO 4 [ 41 , 42 ], respectively. Based on the relative intensity, the weights ratio of the above compounds is 31.0%, 48.7%, and 20.3%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The bonded sample is then placed in a graphite bonding chuck with a pressure of 0.8 MPa applied to it. To complete the wafer bonding process, the wafer pair together with the chuck is annealed in an oven at 300 °C for 8 h in nitrogen ambient …”
Section: Methodsmentioning
confidence: 99%
“…Wafer bonding is considered a promising technique to circumvent this problem, and InP/silicon‐on‐insulator (SOI) wafer bonding has been extensively studied as the hybrid integration platform for photonic integrated circuits (PICs) with excellent performance and novel functionality . Furthermore, adopting Al 2 O 3 as the intermediate layer is reported to improve the bonding strength and thermal properties of bonded samples . In our study on plasma‐assisted InP/Al 2 O 3 /SOI wafer bonding, it is found that the success of bonding relies critically on NH 4 OH treatment of InP wafer.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high dielectric constant, proper electrical property, large band gap, good thermal stability and thermal conductivity, Al 2 O 3 films are widely used as gate dielectrics [1][2][3] or protective layers 4,5) for functional layers transferred to different substrates in the semiconductor industry. In recent years, their applications have been extended to optics, 6) micro-electromechanical systems 7) and protective coatings 8) thanks to its optical, mechanical and barrier properties.…”
Section: Introductionmentioning
confidence: 99%